SLAMF8 expression predicts the efficacy of anti‐PD1 immunotherapy in gastrointestinal cancers. Issue 10 (26th October 2021) - Zhang, Qun; Cheng, Lei; Qin, Yanmei; Kong, Linghui; Shi, Xiao; Hu, Jing; Li, Li; Ding, Zhou; Wang, Ting; Shen, Jie; Yang, Yang; Yu, Lixia; et al.
Abstract: Objectives: Epstein–Barr virus (EBV) infection is associated with a better response to anti‐PD1 immunotherapy. We hypothesised that genetic alterations induced by EBV infection are responsible for the activation of key immune responses and hence are predictive of anti‐PD1 efficacy. Methods: With transcriptome data of gastric cancer (GC), we explored differentially expressed genes (DEGs) specific for EBV infection and performed coexpression network analysis using the DEGs to identify the consistent coexpression genes (CCGs) between EBV‐positive and EBV‐negative GC tissues. We selected the tag genes of the CCGs and validated them using RNA sequencing and immunohistochemistry. We established murine models and collected tissues from clinical patients to test the value of SLAMF8 in predicting anti‐PD1 treatment. The location and expression of SLAMF8 were characterised by multiplex immunofluorescence and quantitative PCR. Moreover, exogenous overexpression and RNA‐sequencing analysis were used to test the potential function of SLAMF8 . Results: We identified 290 CCGs and validated the tag gene SLAMF8 in transcriptome data of gastrointestinal cancer (GI). We observed that the T‐cell activation pathway was significantly enriched in high‐expression SLAMF8 GI cancers. Higher SLAMF8 expression was positively associated with CD8 expression and a better response to anti‐PD1 treatment. We further observed dynamically increased expression of SLAMF8 in murine models relatively sensitive to anti‐PD1 treatment. SLAMF8 was mainly expressed on the surface of macrophages. Exogenous overexpression of SLAMF8 in macrophages resulted in enrichment of positive regulation of multiple immune‐related pathways. Conclusion: Higher SLAMF8 expression may predict better anti‐PD1 immunotherapy efficacy in GI cancer. Abstract : In this study, we found that SLAMF8 was involved in activating the antitumour immune response in gastrointestinal (GI) cancer. Thus, higher SLAMF8 expression may predict better anti‐PD1 immunotherapy efficacy in GI cancer.